Extended version of generalised Lindley distribution - Irshad, M. R.; Maya, R. (South African Statistical Journal, 2017)
In this paper, we consider an extended version of the generalised Lindley distribution (EVGLD). Some mathematical properties of the EVGLD including moments, distribution of the order statistics, inequality measures, different entropy measures and vitality function are derived. The method of moments and method of maximum likelihood estimation are used to estimate the parameters. In addition to this, Fisher information matrix and asymptotic confidence interval are also included. Finally, two real life data sets are considered to illustrate the relevance of the new model and compared it with other forms of Lindley models.